How the Indashyikirwa intimate partner violence prevention programme in Rwanda influenced parenting and violence against children - Stern, Erin (Journal of family violence, 2022)
There is increasing interest in working at the intersections of intimate partner violence (IPV) and violence against children (VAC), especially in the family, yet few programmatic strategies exist or have been evaluated to assess the combined impact of strategies on both types of violence. This paper addresses this gap by exploring the influence that Indashyikirwa—a programme designed to reduce IPV in Rwanda— had on VAC in the families of couples participating in the programme. Indashyikirwa included a 21-session couples’ curriculum, safe spaces for IPV survivors, and community activism against violence. In addition to reductions in IPV, a randomized control trial found significant reductions in parent’s reports of children witnessing IPV, parents’ attitudes condoning harsh physical punishment of children, and parents’ use of corporal punishment as discipline. This paper uses qualitative data to better understand how and why the couples’ curriculum influenced parenting and VAC. Twenty-eight participants (fourteen male-female couples) were individually interviewed at three time points, once before and twice after the couples’ curriculum implementation. Six men and six women who completed the curriculum and subsequently carried out activism were also interviewed at two time points. The data were analyzed thematically. Pathways motivating couples’ attitude and behavior changes towards children included reflecting on the consequences of IPV for children and appreciating the benefits for children of non-violent, gender equitable households. This analysis suggests that working with co-habiting couples presents a viable strategy for working to prevent IPV, VAC and promote more gender equitable family dynamics.